Teachers' Beliefs And Levels Of Use In The Adoption Of The Student-Active Learning Approach In EFL Classrooms In Oman - Al Shekaili, Bati Sulaiman Humaid (2014)

(untitled)
The main purpose of the study was to investigate the teachers' Beliefs and their Levels of Use (LoU) in the adoption of the Student-Active Learning (SAL) approach in their English as a Foreign Language (EFL) classrooms in Oman. It was also aimed to investigate the challenges encountered by the teachers in the adoption of the SAL approach. Matlamat utama kajian ini adalah menyelidik kepercayaan guru dan Tahap Penggunaan (TP) kaedah Pemelajaran Aktif-Pelajar (PAP) di bilik darjah EFL di Oman. Kajian ini juga turut menyelidik cabaran yang dihadapi oleh para guru dalam merealisasikan kaedah PAP.